Peer Health Educator for Escalating Adolescent Health Education Based On Mobile Health - Julia Pertiwi; Syefira Ayudia Johar; Rika Andriani (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
Adolescents are vulnerable to physical and mental health problems. Lack of health information makes adolescents influenced by misinformation, which can trigger detrimental things. Main issues of this topic are lack of information about adolescent nutrition and mental health, unbalanced food consumption patterns, negative stigma related to adolescent mental health, and lack of use of mobile health. These problems caused by limited access to health information and absence of health educators in schools. The solution offered were education and training on adolescent nutrition and mental health. This activity aimed to improve knowledge and skills of adolescent with mobile health-based health education. Community service activities are carried out through peer health educator training, adolescent nutrition education, mental health education, and training of mobile health applications. The implementation method was carried out with preparation, socialization, training and application of technology, evaluation, and program sustainability planning. Results showed an increase in knowledge from an average pretest of 45,19 to a posttest of 87,51. Participants were skilled in using digital health-based applications for adolescent nutrition and mental health. In addition, peer health educator training demonstrated efficient health communication skills. Recommendations for sustainability were school management collaborate with Baki Health Center to held education for other adolescent health topics and optimize school health unit.